ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS NASABAH PADA BANK BRI UNIT PANJI DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Zulaeha, Iradatus; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
In general, marketing is an activity that creates and delivers goods or services to consumers. It is a process by which companies create value for customers and build strong customer bases to capture value from customers in return. Marketing is an organizational function and set of processes for creating, communicating and delivering value to customers and cultivating customer relationships in ways that benefit the organization and its specific interests for BRI Unit Panji customers by increasing the needs of people in Situbondo. The purpose of this study is to analyze and test factors which influence customer satisfaction at Bank BRI Panji with customer satisfaction as an intervening variable. The population in this study are customers of BRI Unit Panji in Situbondo. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study use Partial Least Square - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis testing that used the Smart PLS 3.0 application showed that communication has a significant positive effect on customer satisfaction, products have a significant positive effect on customer satisfaction, communication has a positive but not significant effect on customer loyalty, products have a positive but not significant effect on customer loyalty. Customer satisfaction has a significant positive effect on customer loyalty, communication has a positive but not significant effect on customer loyalty through customer satisfaction, products have a significant positive effect on customer loyalty through customer satisfaction.